The Position of Selected English Dominicans Towards the Immaculate Conception in the Pre-tridentine Era - Beyga, Paweł (Verbum Vitae, 2024)
The Immaculate Conception of the Mother of Christ is a truth of the Catholic faith that was only dogmatised by Pius IX in 1854. Until then, there had been debate among theologians regarding this Marian privilege. By means of selected examples the article shows the attitude of English Dominicans to the Immaculate Conception of Mary between the 13th and 16th centuries. It transpires that the members of the Order of Preachers in the British Isles presented an extremely diverse positions. One can find both strongly dissenting positions and those manifestly in favour of the Immaculate Conception. It is extremely interesting to note that in their arguments for the Immaculate Conception, some Dominicans distanced themselves from the continental theology represented by Aquinas. The way the Dominicans conceptualised the Immaculate Conception was closer to that represented by the twelfth-century theologian and historian Eadmer.